Effects on phacoemulsification efficiency and chatter at variable longitudinal ultrasound settings when combined with constant torsional energy. Issue 5 (May 2020) - Bohner, Austin; Peterson, John S.; Wright, Alex J.; Mamalis, Christina; Bernhisel, Ashlie; Zaugg, Brian; Barlow, William R.; Olson, Randall J.; Pettey, Jeff H.
Abstract : Purpose: To evaluate longitudinal power settings for optimally efficient lens fragment removal, using the Centurion machine. Setting: John A. Moran Eye Center, University of Utah, Salt Lake City, USA. Design: Experimental study. Methods: Porcine lens nuclei were cut into 2.0 mm cubes. Experiments were conducted at 100% torsional power; vacuum set at 500 mm Hg, aspiration 50 mL/min, and intraocular pressure 110 mm Hg. A 20-degree tip with a 30-degree bevel was used. Longitudinal power was tested between 20% and 100%. Efficiency (time for fragment removal) and chatter (the number of times the fragment bounced from the tip) were measured. Results: A linear increase in efficiency was observed from 20% to 100% longitudinal power (R 2 = 0.9281, slope = −0.0271). An efficiency slope change occurred at 60% power, with the largest incremental change in efficiency between 20% and 60% (R 2 = 0.9756, slope = −0.0394) and a lesser change between 60% and 100% (R 2 = 0.9827, slope = −0.0121). Chatter analysis showed minimal events at 20% to 60%, but a significant increase at >80% ( P = .005). This increase appeared to be incremental (R 2 = 0.8929). Conclusions: Increasing longitudinal power, with all other settings constant, increased efficiency. Greatest efficiency gains were observed between 20% and 60%. At 80% and 100%, chatter events increased significantly. With a goal of recommending optimally efficient settings while minimizing excess energy and chatter, adding 60% of longitudinal power to 100% torsional power was shown to be the best setting to increase efficiency and avoid repulsion in these vacuum and aspiration settings.